A Combinatorial Vaccine Containing Inactivated Bacterin and Subunits Provides Protection Against Actinobacillus pleuropneumoniae Infection in Mice and Pigs - Zhang, Lijun; Luo, Wentao; Xiong, Ruyue; Li, Haotian; Yao, Zhiming; Zhuo, Wenxiao; Zou, Geng; Huang, Qi; Zhou, Rui (Frontiers in Veterinary Science, 2022)
Actinobacillus pleuropneumoniae is the etiological agent of porcine contagious pleuropneumonia that causes great economic losses in the swine industry. Currently, vaccination is still a commonly used strategy for the prevention of the disease. The commercially available vaccines of this disease, including inactivated bacterins and subunit vaccines, have clinical limitations including side effects and low cross-protection. In this study, a combinatorial vaccine (Bac-sub) was developed, which contained the inactivated bacterial cells of a serovar 1 strain and three recombinant pro-toxins (rApxIA, rApxIIA, and rApxIIIA). Its side effects, immune protection, and cross-protection were evaluated and compared with a commercial subunit vaccine and a commercial trivalent bacterin in a mouse infection model. The results revealed that Bac-sub vaccine did not show obvious side effects, and induced higher levels of Apx toxins-specific IgG, IgG1, and IgG2a than the commercial vaccines after boosting. After challenge with the virulent strains of serovars 1, 5, and 7, the Bac-sub vaccine provided higher protection (91.76%, 100%, and 100%, respectively) than the commercial vaccines. Much lower lung bacterial loads and milder lung lesions were observed in the Bac-sub vaccinated mice than in those vaccinated with the other two vaccines. The protective efficacy of the Bac-sub vaccine was further evaluated in pigs which showed that the vaccinated pigs displayed significantly milder clinical symptoms and lung lesions than the non-vaccinated pigs after the challenge. Taken together, Bac-sub is a safe and effective vaccine that could provide high protection against A. pleuropneumoniae infection in mice as well as pigs.